MANAGEMENT OF MAIZE STOVER WITH UNDERDOSES RATES OF GLYPHOSATE APPLICATIONS IN NO-TILLAGE - Jasper, S. P.; Picoli Jr, G. J. [UNESP]; Velini, E. D. [UNESP]; Sousa, S. F. G. [UNESP]; Carbonari, C. A. [UNESP] (Univ Federal Vicosa, 2015)
Glyphosate has significant effects on the growth and development of plants when in underdoses. This work was developed to verify the effect of the application of glyphosate in underdoses in lignin synthesis and consequently decomposition of maize stover. Two experiments were conducted; the first one in a greenhouse for underdoses adjustments and the second one in the production area. The experimental design of the first trial was completely randomized with four replications. The treatments consisted in the application of the underdoses: 0, 25, 50 and 100 g ha(-1) of glyphosate. In the production area, the experimental design was a randomized block with four replications, in underdoses: 0, 12.5, 25 and 50 g ha(-1). The results were submitted to analysis of variance and regression. The underdoses of 25 g a.e. ha(-1) in a greenhouse promoted 36% increase in productivity of stover, in addition to increasing the lignin content in 16%, with no change in the unwanted growth of maize plants. In the production area, the concentration of 12.5 g a.e. ha(-1) of glyphosate reduced the lignin content and the other underdoses have not changed this feature in maize plants. None of the underdoses affected the height and biomass produced by the maize plants. The highest underdose tested promoted acceleration in the decomposition of maize stover.
Keywords: Zea mays; stover decomposition; lignification; growth stimulus